1978
DOI: 10.1111/j.1365-2133.1978.tb07061.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical betamethasone 17-valerate is an anticorticosteroid in the rat.

Abstract: In the oxazolone-induced delayed hypersensitivity inflammation in the rat ear, betamethasone 17-valerate, in contrast to other topical corticosteroids, is incapable of suppressing oedema. When given in combination with triamcinolone acetonide, betamethasone 17-valerate competitively antagonizes the anti-inflammatory action of the active steroid. When tested in the mouse, betamethasone 17-valerate behaved as an anti-inflammatory agent 15 and 80 times as potent as betamethasone and hydrocortisone respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The explanation for these unusual results almost certainly lies in the choice ofthe rat as a model. Recent studies have indicated that in the rat betamethasone 17-valerate acts as an anti-cortlcostcroid (Young, Yoxall & Wagner, 1978;Young, Wagner & Fisk, 1978). Thus, in a dermal atrophy assay, an anti-inflammatory assay and in vitro lymphocyte transformation assay betamethasone 17-valcrate was less active than hydrocortisone.…”
Section: Measurement Of the Atrophogenic Properties Of Corticosteroidsmentioning
confidence: 99%
“…The explanation for these unusual results almost certainly lies in the choice ofthe rat as a model. Recent studies have indicated that in the rat betamethasone 17-valerate acts as an anti-cortlcostcroid (Young, Yoxall & Wagner, 1978;Young, Wagner & Fisk, 1978). Thus, in a dermal atrophy assay, an anti-inflammatory assay and in vitro lymphocyte transformation assay betamethasone 17-valcrate was less active than hydrocortisone.…”
Section: Measurement Of the Atrophogenic Properties Of Corticosteroidsmentioning
confidence: 99%